(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bharati Mukherjee is an Indian-born American writer. She is one of the prominent novelist of Indian Diaspora. She created a fair place for herself in the literary circle abroad, by her contribution of Indian English writing. This paper explore identity crisis and quest for identity in Bharati Mukherjee’s novel ‘Wife’. The search for identity of immigrants experiences of the clash of cultures and questions of identity, the immigrants face at that time in an alien land are one of the major concerns of Bharati Mukherjee’s novels. Her novels are often reveals the contemporary themes. One of these themes is search for their true identity.